Analysis of Construction Operations for The Development of High Speed Railway Jakarta-Bandung (Project Team Section 3 using The Cement Fly- Ash Gravel Pile Methode) - Putri, Ananda Agneshia; Pratama , Yuda Andika; Ginting, Emanuella; Abrar, Nisrina (UNIB Press, 2025)
Construction operation modeling is carried out to understand the behavior of the construction operating system better. Further, construction operation modeling can provide an overview of productivity and duration of completion, as well as make it easier to solve problems from the perspective of the whole model. In this paper, we conduct a CYCLONE modeling simulation in construction operations on the PT Kereta Cepat Indonesia China (KCIC) Project to build the Jakarta-Bandung High Speed Railway (Jakarta- Bandung / KCJB Fast Train using CFG Pile Construction operations. The CFG Pile construction in section 3 is carried out for 21,000 points and has repeated construction work so that it can perform a cyclone method simulation using productivity analysis with the help of MATLAB software (Simulink-Simevent). This simulation is executed for 30 cycles until the productivity results from the simulation have reached steady state conditions. Productivity result from both softwares produce almost the same results, respectively 0.675 from the COST program and 0.7427 from the MATLAB program. Based on the results of the sensitivity analysis, it can be concluded that the addition of resources such as number of drilling rigs, concrete pumps, and mixes truck will increase project productivity.